Modulation of lactate-lysosome axis in dendritic cells by clotrimazole potentiates antitumor immunity. Issue 5 (20th May 2021) - Wang, Zining; Xu, Feifei; Hu, Jie; Zhang, Hongxia; Cui, Lei; Lu, Wenhua; He, Wenzhuo; Wang, Xiaojuan; Li, Mengyun; Zhang, Huanling; Xiong, Wenjing; Xie, Chunyuan; et al.
Abstract : Background: Dendritic cells (DCs) play a critical role in antitumor immunity, but the therapeutic efficacy of DC-mediated cancer vaccine remains low, partly due to unsustainable DC function in tumor antigen presentation. Thus, identifying drugs that could enhance DC-based antitumor immunity and uncovering the underlying mechanism may provide new therapeutic options for cancer immunotherapy. Methods: In vitro antigen presentation assay was used for DC-modulating drug screening. The function of DC and T cells was measured by flow cytometry, ELISA, or qPCR. B16, MC38, CT26 tumor models and C57BL/6, Balb/c, nude, and Batf3 −/− mice were used to analyze the in vivo therapy efficacy and impact on tumor immune microenvironment by clotrimazole treatment. Results: By screening a group of small molecule inhibitors and the US Food and Drug Administration (FDA)-approved drugs, we identified that clotrimazole, an antifungal drug, could promote DC-mediated antigen presentation and enhance T cell response. Mechanistically, clotrimazole acted on hexokinase 2 to regulate lactate metabolic production and enhanced the lysosome pathway and Chop expression in DCs subsequently induced DC maturation and T cell activation. Importantly, in vivo clotrimazole administration induced intratumor immune infiltration and inhibited tumor growth depending on both DCs and CD8+ T cells and potentiated the antitumor efficacy of anti-PD1 antibody. Conclusions: Our findings showed that clotrimazole could trigger DC activation via the lactate-lysosome axis to promote antigen cross-presentation and could be used as a potential combination therapy approach to improving the therapeutic efficacy of anti-PD1 immunotherapy.